1981
DOI: 10.1007/bf00387820
|View full text |Cite
|
Sign up to set email alerts
|

Cereal ?-amylase: Immunochemical study on two enzyme-deficient inbred lines of rye

Abstract: Two inbred lines of rye (Secale cereale L), the kernels of which displayed a very low level of β-amylase activity (1-3% of the levels generally found in rye), were investigated in comparison with a third normal line. An anti-wheat β-amylase immune serum which cross-reacted with the rye enzyme was used in this study.The anti-wheat β-amylase immune serum absorbed the β-amylase activity in the three lines which were investigated. Comparably small amounts of enzymatic antigen corresponded to the small levels of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
2

Year Published

1990
1990
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 8 publications
1
23
0
2
Order By: Relevance
“…However, the effects of the available soybean (Hildebrand and Hymowitz, 1981) and rye (Daussant et al, 1981) mutations on vegetative development have not been well characterized. In addition, previously identified Arabidopsis mutants with alterations in ␤-amylase activity carry defects in genes involved in ␤-amylase regulation rather than in ␤-amylase structural genes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the effects of the available soybean (Hildebrand and Hymowitz, 1981) and rye (Daussant et al, 1981) mutations on vegetative development have not been well characterized. In addition, previously identified Arabidopsis mutants with alterations in ␤-amylase activity carry defects in genes involved in ␤-amylase regulation rather than in ␤-amylase structural genes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of ␤-amylasedeficient lines of soybean (Glycine max; Hildebrand and Hymowitz, 1981) and rye (Secale cereale; Daussant et al, 1981) have focused primarily on characterizing the effects of reduced ␤-amylase activity on seed formation and germination. These studies reveal no evidence for an essential role of ␤-amylases in carbohydrate metabolism of developing or germinating soybean seeds (Hildebrand and Hymowitz, 1981) or in germination of rye seeds (Daussant et al, 1981). Little work has been done to determine whether the decreased ␤-amylase activity levels in these plant lines affect later, vegetative, stages of development.…”
mentioning
confidence: 99%
“…The mutant line is highly deficient in f3-amylase having less than 1% of the activity present in the normal line kernels. This deficiency is due to a lack of enzymatic protein synthesis (5). In a study on barley mutants exhibiting either a large excess or deficiency in f3-amylase activity, it was shown that two types of mRNA were involved in the synthesis of the endosperm fl-amylase and that the excess or the deficiency was due to a modulation in the endosperm mRNA synthesis (9).…”
Section: Discussionmentioning
confidence: 99%
“…Electrophoresis was carried out at 40C and 5 V cm-' for 15 h. After electrophoresis the gels were stained for amylase activity using soluble starch as substrate (5).…”
Section: Immune Serumsmentioning
confidence: 99%
“…In addition to sweet potato, β-amylase-deficient phenotypes have been identified in soybean Hymowitz 1980, 1981), rye (Daussant et al 1981, Sadowski and Daussant 1989, barley (Kreis et al 1987, Kihara et al 1999, Kaneko et al 2000, rice (Yamaguchi et al 1999), wheat (Allison et al 1978, and Arabidopsis (Laby et al 2001). In most cases, studies of β-amylase null mutants have shown that the differences in enzyme activity lie in the β-amylase genetic structure, but no study has focused on the translational, transcriptional, or genetic structural control of the β-amylase null phenotypes in sweet potato.…”
Section: Introductionmentioning
confidence: 99%